Enklitika in den deutschen Mundarten Mährens und Schlesiens - Mojmír Muzikant (Linguistische Treffen in Wrocław)
The present article examines the realization of personal pronouns in spoken language in the dialectal territory of Moravia and Silesia. The scope of the pronoun forms studied is limited by their occurrence in seven sentences (see below), which were explored using a direct method based on questionnaires for the Linguistic Atlas of German Dialects in the Czech Republic. It turned out that in addition to accented and unaccented forms, reduced pronoun forms (enclitics) are not infrequently used. In the following discussion, individual variants of enclitics are presented, including their territorial characteristics. The extent to which the individual sub-areas of a given dialect territory are defined by the identified pronoun forms (both unabbreviated forms and enclitics) is also examined. (des), (eis) denotes that the Jihlava, Brno and Vyškov language islands are under the influence of Bavarian dialects, from reduced forms, which are clearly predominant compared to the unreduced forms, although their considerable variability and dispersion throughout the study area make unambiguous territorial assignment difficult, the accusative of the personal genitive pronoun er is characterized by the enclitic variant in Javorník (Jauerniger Ländchen) and along the western border of northern Moravia. Also, the enclitic variant b instead of wir (1st person plural) can be attested only in North Moravia with one exception. Furthermore, it appears that the Hrebečsko region (Schönhengst) is closer to North Moravia than to the islands in South Moravia in terms of the repertoire of enclitic variants. This complements to some extent Volume V “Morphology” (2020: 142–145) of the Language Atlas (“Atlas der deutschen Mundarten in Tschechien”, 2014–2020), which does not treat personal pronouns with the exception of er and Ihnen (the polite form).